Kapabilitas Pemerintah Desa dalam Pengelolaan Dana Desa di Kecamatan Pemalang - Wendy Resnu; Tri Yuniningsih; Retno Sunu Astuti; Teuku Afrizal (Universitas Medan Area, 2022)
The Village Fund as one of the programs that began to be implemented in the era of President Joko Widodo certainly had a major impact on changing the face of the village. Village funds sourced from the State Revenue and Expenditure Budget are one of the sources of village income used for village infrastructure development and village community empowerment in an effort to realize village progress and community welfare. The management of the Village Fund, starting from the planning, implementation to accountability reporting stages, of course, must be guided by the provisions of the applicable laws and regulations, as an effort to realize a clean, transparent and accountable Village Fund management. In line with this, of course, it takes human resources from the village government (village heads and village officials) who are qualified, capable and capable in carrying out their respective duties and responsibilities. The problem raised in this research is the relationship between the capability of the village government and the successful management of a clean, transparent and accountable Village Fund. The conclusion of this research is that the capability of the village government is directly proportional to the success of the village concerned in realizing a clean, transparent and accountable management of the Village Fund.